Ketidak-Mutlakan Laki-laki dalam Perwalian Nikah Menurut Persepektif Ulama Tafsir - Nasaiy Aziz (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Marriage is legal action which needs basic principles that make it legally  valid. Of the basic principles of marriage, the existence of guardian always  becomes a complicated problem in the community. The majority of jurists argued that a woman should not marry himself or others. If she marry without a guardian, then the marriage null and void. However, differed with the majority of jurists Abu Hanifa argued that the female adult of normal intelligence has the right to perform the marriage ceremony without a guardian directly, both girls and widows. This is based on al-Baqarah verse 230; 232 and 234. In the third verse is attributed to the contract of women, this suggests that women have the right to perform marriages directly. Differences of opinion among the commentators that  occurs is due to the lack of texts that clearly states the problem of wali concept itself.